Successful Aging and Learning a Foreign Language - Tanja Gradečak (Društvene i Humanističke Studije)
The Activity Theory proposed by Havighurst (1963) suggests that successful aging is achieved when older adults remain active and maintain social interactions. The quality of life, an individual’s adaptation to aging and a sense of well-being are closely related to the preservation of previous social habits, as well as to the level of physiological, psychological and cognitive activities. One of the cognitive abilities that can contribute to maintaining a satisfactory level of active aging is learning a foreign language, and this research shows some preliminary results about the effects of learning English as a foreign language on the sense of well-being of retired older adults. After a discussion on the definition of the term ‘older adult’ and an overview of the theoretical background of aging through the Theory of Detachment, Activity and Continuity, respectively, the results of a study conducted on 80 participants of an English language course for retired elderly persons were presented using a questionnaire with open-ended questions and assessment questions which examines socio-affective factors in the process of learning English. It is structured in its basic elements according to the survey conducted in Pfenninger and Polz (2017: 6) on the effect of a foreign (L2) language course on socio-affective factors, i.e. students’ motivation to learn English in the older age. The results indicate that there are certain age limitations of the human ability to learn foreign languages, as well as age differences in foreign language learning, but that high motivation and a sense of intellectual satisfaction as well as interaction with the lecturer and other participants during the learning process contribute to the feeling of well-being of the participants.